Torrefaction of woody biomass (Acacia nilotica): Investigation of fuel and flow properties to study its suitability as a good quality solid fuel - Singh S.; Chakraborty J.P.; Mondal M.K. (My University, 2025)
Torrefaction of Acacia nilotica was carried out in a quartz fixed-bed reactor. Temperature and residence time varied from 220 to 280 °C and 20–60 min. The fuel (volatile ignitability (VI), combustibility index (CI), fuel ratio (FR)), and flow (Hausner ratio (HR), cohesion coefficient (C), Carr compressibility index (CCI), angle of repose) properties were investigated for raw and torrefied biomass. Torrefied biomass was also characterized through TGA, FTIR, SEM-EDX and ICP-MS analysis. For moisture sorption test, contact angle was measured. Finally, torrefied biomass was compared with coal using published literature. The HHV, fixed carbon content, FR of raw biomass at 280 °C for 40 min was increased from 19.31 to 24.76 MJ/kg, 11.35 to 60.40 wt %, and 0.13 to 1.63, respectively. While, VI, CI, C, CCI and bulk density of raw biomass at similar condition of torrefaction decreased from 15.76 to 15.37 (MJ/kg), 147.40 to 17.37 (MJ/kg), 0.40 to 0.33, 22.85 to 15.86 and 230.82 to 172.84 (kg/m3), respectively. ICP-MS analysis revealed that torrefied biomass was enriched in sodium, potassium, calcium, magnesium, etc. At similar torrefaction condition, the moisture absorbed by raw and torrefied biomass was 35.44% and 6.61%, respectively. Contact angle (79.1°/77.5°) for torrefied biomass suggested its hydrophobic nature. © 2020 Elsevier Ltd